Lactarius brunneocinnamomeus, a new species of Lactarius subgenus Russularia from West Bengal, India - Paloi, Soumitra; Verbeken, Annemieke; Acharya, Krishnendu (Phytotaxa, 2019)
Lactarius brunneocinnamomeus found in Shorea robusta (‎Dipterocarpaceae) dominated forest, is proposed as a new species. The species belongs to L. subg. Russularia, sect. Russularia. It is easily recognized by a light brown to orange brown pileus with concentric zones, milky white latex and a palisade to trichopalisade as a pileipellis. Its phylogenetic position inside the genus is based on the nuclear internal transcribed spacer (ITS) region. A complete description, drawings and photographs of the new species are provided. The new species is compared with morphologically similar and phylogenetically allied species.